Computational Intelligence International Joint Conference, IJCCI 2015 Lisbon, Portugal, November 12-14, 2015, Revised Selected Papers - Merelo, Juan Julián; Rosa, Agostinho; Cadenas, José M.; Correia, António Dourado; Madani, Kurosh; Ruano, António; Filipe, Joaquim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book includes a selection of revised and extended versions of the best papers from the seventh International Joint Conference on Computational Intelligence (IJCCI 2015), held in Lisbon, Portugal, from 12 to 14 November 2015, which was composed of three co-located conferences: The International Conference on Evolutionary Computation Theory and Applications (ECTA), the International Conference on Fuzzy Computation Theory and Applications (FCTA), and the International Conference on Neural Computation Theory and Applications (NCTA). The book presents recent advances in scientific developments and applications in these three areas, reflecting the IJCCI's commitment to high quality standards.
AI Researchers, Video Games are Your Friends! -- On Routine Evolution of New Replicating Structures in Cellular Automata -- Application of Adaptive Differential Evolution for Model Identification in Furnace Optimized Control System -- Multi-Strategy Genetic Algorithm for Multimodal Optimization -- GPGPU Vs Multiprocessor SPSO Implementations to Solve Electromagnetic Optimization Problems -- Multi-Robot Cooperative Tasks using Combined Nature-Inspired Techniques -- GEML: Evolutionary Unsupervised and Semi-Supervised Learning of Multi-class Classification with Grammatical Evolution -- For Sale or Wanted: Directed Crossover in Adjudicated Space -- Design of an Autonomous Intelligent Demand-Side Management System by using Electric Vehicles as Mobile Energy Storage Units by Means of Evolutionary -- Particle Convergence Time in the PSO Model with Inertia Weight -- A Modified Fuzzy Lee-Carter Method for Modeling Human Mortality -- Synchronization of Uncertain Chaotic Systems using Generalized Predictive Control based on Fuzzy PID Controllers -- An Order Hyperresolution Calculus for Gödel Logic with Truth Constants and Equality, Strict Order, Delta -- Using Evidence Theory in Land Cover Change Prediction to Model Imperfection Propagation with Correlated Inputs Parameters -- Choosing Suitable Similarity Measures to Compare Intuitionistic Fuzzy Sets that Represent Experience-Based Evaluation Sets -- Bayesian Logistic Regression using Vectorial Centroid for Interval Type-2 Fuzzy Sets -- A Comparison of Learning Rules for Mixed Order Hyper Networks -- Pedestrian Action Prediction using Static Image Feature -- Gaussian Nonlinear Line Attractor for Learning Multidimensional Data -- Mining Significant Frequent Patterns in Parallel Episodes with a Graded Notion of Synchrony and Selective Participation -- A Heteroassociative Learning Model Robust to Interference -- AnExtended Q Learning System with Emotion State to Make Up an Agent with Individuality -- Inedited SVM Application to Automatically Tracking and Recognizing Arm-and-Hand Visual Signals to Aircraft -- Learning-Based Distance Evaluation in robots' vision: A Comparison of ANFIS, MLP, SVR and Bilinear Interpolation Models.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence